Analysis of the Development and Key Technologies of Hypersonic Defense Capability in Foreign Countries - Wang Enliang, Yuan Cheng, Zhao Yujie, Gao Shuliang (Hangkong bingqi, 2024)
With the rapid development and application in practical battlefields of hypersonic weapons, the demand for hypersonic defense technologies has become increasingly urgent in various countries. Due to the different target characteristics of hypersonic weapons from traditional missiles, existing missile defense systems are difficult to achieve good interception effects, and related equipment and technologies need to be redeveloped. In order to sort out the future demand directions of hypersonic defense technologies, this paper summarized the current status of hypersonic defense capabilities in countries such as the United States, Russia, and Japan from the aspects of early warning detection, interception and strike and so on, and analyzed relevant key technologies. It is proposed that future hypersonic defense should focus on increasing interception distance, reducing combat costs, and dealing with system attack.